A taxonomic revision of the southern African native and naturalized species of Silene L. (Caryophyllaceae) - Manning, J.C.; Goldblatt, Peter (African Biodiversity & Conservation, 2012)
The native and naturalized species of Silene L. in southern Africa are reviewed, with full synonomy and the descriptionof two new species from the West Coast of Western Cape. Eight native species and three naturalized species are recognized,including the first identification in southern Africa of the Mediterranean S. nocturna L. The identity of S. aethiopica Burm.,which has remained unknown since its description, is established and is found to be the oldest name for S. clandestina Jacq.Patterns of morphological variation within each species are discussed and subspecies are recognized for geographically segregated groups of populations that are ± morphologically diagnosable. The following new names or combinations are madeamong the southern African taxa: S. aethiopica subsp. longiflora; S. burchellii subsp. modesta, subsp. multiflora, and subsp.pilosellifolia; S. crassifolia subsp. primuliflora; S. saldanhensis; S. rigens; and S. undulata subsp. polyantha. Each taxonis described, with information on ecology and distribution, and most species are illustrated, including SEM micrographs ofthe seeds.